Third-Year Student Nurses: Coping With The Challenges Of Management Postings In Private Universities - Tulasi, Dewi Visuranathan * (Social Health Analytics Sdn Bhd, 2024)
By embracing a growth mindset, building strong support networks, mastering time management, and developing leadership skills, student nurses are well-prepared to meet the challenges of their profession. The final year of nursing education marks a significant milestone for student nurses. For third-year students in private universities, the culmination of their training often involves a rigorous management posting.